Peran Kepala Madrasah Dalam Meningkatkan Kinerja Guru di MIN 2 Pasuruan - Hariyono (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to answer questions about the problem formulation: first, about the role of Madrasah Heads in improving Teacher performance; second, supporting factors and inhibiting factors for Madrasah Heads in improving teacher performance. In order to find out the problem and obtain accurate data, researchers used observation methods (field observations), interviews or interviews and documentation. By using qualitative descriptive analysis techniques. From this research it can be said that the role of the head of the madrasah, especially at the MIN 2 Pasuruan institution, plays a more active role because of the nature of women who tend to be motherly and protective of the madrasah residents. The madrasa head has carried out his role as an educator and manager. administrator, supervisor, leader, innovator and motivator. The supporting factors regarding the role of madrasah heads in improving teacher performance are: Discipline and enthusiasm of madrasah residents in the learning process. Adequate facilities. The hopes and enthusiasm of the teachers are to make madrasah superior compared to other schools. Meanwhile, the inhibiting factor in improving teacher performance is the diversity of students' different characters. teacher commitment, human resources and IT skills possessed by teachers.